Position of the Syrian Refugee Children in Printed Media - Akgul Gok, Fulya; Gökçearslan Çifci, Elif (Border Crossing, 2017)
Associated with globalization, transformation and mobility all around the world may result in positive and negative impacts on welfare of the countries as well as on psycho-social and economic positions of the individuals. Especially in under developed and developing countries, such effects are more evident. The individuals living in these countries are forced to leave their homeland and become refugees in some other countries due to social, economic, psychological and environmental effects. Migration process has become a threat for physical, psychological, social, economic and cultural development of these children at present and in the future. This study is a content analysis on the position of Syrian children and how they are mentioned in three mainstream newspapers in Turkey (March-April-May 2016). These newspapers are Star, Hürriyet and Cumhuriyet. Only headlines were analyzed and columns were not taken into consideration. News from these papers are categorized according to subjects and contents and then sub-categories were composed. How Syrian children in Turkey have been generally mentioned, on which occasions they have been mentioned and which of their problems have been stated in printed media were analyzed in this study.